Oxidative Stress in Diabetic Neuropathy - Sofia Alexandrina Queirós da Cunha (2015)
For treating chronic pain, a multifactorial condition, is needed a suitable diagnosis which allows the differentiation in its many components. Diabetic neuropathy is a worldwide disease with great impact in the modern society. Diabetes may leads to the production of reactive oxygen species that are associated to oxidative stress, which may be a key factor in the development of diabetic neuropathy. The main goal is to inquire a potential association between chronic pain, diabetic neuropathy and oxidative stress. Thus, was performed a meta-analysis that permitted the causal evaluation between oxidative stress and diabetic neuropathy, and, a pain evaluation was accomplished in a convenience sample using validated surveys – Brief Pain Inventory (BPI) and Douleur Neuropathique 4 (DN4). Through the meta-analysis it was possible evaluate oxidative stress biomarkers, such lipid peroxidation, superoxide dismutase and catalase activities, and reduced glutathione. 9 studies were selected and all were performed in mouse models. The levels of lipid peroxidation were increased in all the studies, however the levels of the other biomarkers were diminished in diabetic models comparatively to healthy controls. In the evaluation of convenience sample, 84 surveys were collected along the four seasons: summer, autumn, winter and spring. The pain complaints were described in terms of local, intensity, impact, relief by medication and its effect on daily activities using BPI questionnaire. The scores obtained in BPI indicate the presence of moderate to severe pain, with increased complaints in autumn and spring, and implications in daily activities, transversal to all groups. To determine the main features associated with neuropathic pain it was used DN4 questionnaire. The DN4 indicated the presence of nearly 50% of patients with neuropathic pain. The results suggest that being female, the increased age and being retired can influence chronic pain and neuropathic pain in patients. As main conclusions, it was possible to verify an association between oxidative stress, and neuropathic pain, and, also, that weather conditions may influence the pain complaints and its prevalence.